Prevalence and Associated Factors of Geriatric Syndromes Among Older Adults in Southern Kyrgyzstan (Asian Journal of Pharmaceutics (AJP), 2025)
Geriatric syndromes (GSs) are complex clinical conditions that significantly affect morbidity andmortality in older adults. This cross-sectional study aimed to evaluate the occurrence of GSs and determine thefactors associated with multiple GSs among 570 older adults aged 65–94 years in the southern region of theKyrgyz Republic. Methods: Participants underwent a comprehensive geriatric evaluation to examine frailtysyndrome, depression, malnutrition, orthostatic hypotension, urinary incontinence, fecal incontinence, cognitiveimpairment, basic dependence in daily activities, falls, visual impairment, hearing impairment, sensory deficits,and chronic pain syndrome. Results: 90.4% of the participants had at least one GS, with 76.2% experiencingtwo or more. The most prevalent GSs were visual and hearing impairment, chronic pain syndrome, dependencyin daily life, cognitive impairment, depression, urinary incontinence, malnutrition, and risk of malnutrition. Theprevalence of frailty syndrome was 25.2%, whereas pre-frailty was observed in 31.5% of the cases. Factorsassociated with frailty syndrome included being female, older age, poor socioeconomic conditions, living alone,and lower levels of education. Oral health evaluation revealed a high prevalence of periodontal disease, boneloss, and edentulousness. Conclusion: The findings highlight the need for comprehensive geriatric evaluation,collaborative care models, and preventive measures in primary healthcare to reduce the impact of geriatricconditions and improve the quality of life of Kyrgyzstan’s elderly population